1992
DOI: 10.1055/s-2007-1021277
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Hematological and Endocrinological Parameters during Repeated Intense Short-Term Running in Comparison to Ultra-Long-Distance Running

Abstract: In order to see the differences in the acute effects of two kinds of running on biochemical, hematological and hormonal parameters, we investigated in one 24 h race (same exterior conditions) two groups of runners (NR = nonstop runners; RR = relay runners). From each participant blood samples were taken before, 3 times during and after the race. In both groups the lipid parameters cholesterol, triglycerides and LDL-cholesterol declined significantly, triglycerides even to 40% of their initial value, whereas HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
22
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
8
22
0
Order By: Relevance
“…The only change observed post-competition was an increase in hematocrit, possibly as a result of the hemodilution phenomenon. This finding agrees with Nagel et al 19 who observed a decrease of hematocrit in runners after long distance events. Contrarily, Shinkai et al 4 and Rodrigues 6 did not detect changes in hematocrit in long-distance runners after a competition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The only change observed post-competition was an increase in hematocrit, possibly as a result of the hemodilution phenomenon. This finding agrees with Nagel et al 19 who observed a decrease of hematocrit in runners after long distance events. Contrarily, Shinkai et al 4 and Rodrigues 6 did not detect changes in hematocrit in long-distance runners after a competition.…”
Section: Discussionsupporting
confidence: 93%
“…Contrarily, Shinkai et al 4 and Rodrigues 6 did not detect changes in hematocrit in long-distance runners after a competition. Conflicting results regarding hemoglobin concentration in athletes have been reported in the literature, with the results ranging from unchanged 20 and increased 4 to reduced post-effort levels 19 . Taken together, the present results suggest that a BJJ competition is less likely to severely affect red blood cell counts and related measures.…”
Section: Discussionmentioning
confidence: 99%
“…Spearman's correlation coefficient was used to determine the association between changes in endocrine and metabolic outcomes and energy balance. Based on previously published changes in metabolic hormones during prolonged strenuous exercise as well as previous findings from our laboratory, a sample size of n=7 was deemed sufficient to detect changes in leptin, IGF-1, and testosterone of 32%, 57%, and 53%, respectively [9][10][11]24 at p<0.05 at a power of 0.8, and a sample size of 11 was deemed energy balance in this group was largely driven by ad libitum caloric intake. We previously identified caloric intake from solid foods as an important predictor of energy intake, since those athletes who managed to consume more energy from solid foods were more likely to remain in energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…The fall in iron levels may also be due to the infl ammatory response as a result of muscle damage [10] , which is very usual in elite sportsmen [36] . This infl ammatory response causes a redistribution of iron in the reticule endothelial system and leads to a decrease in serum iron concentration [37,38] .…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, they suffer the so-called hand disease (hand ache and infl ammation) as a consequence of either the bad placing of protections on their hands or a bad striking technique. Serum iron levels have been reported to be lower both in endurance and strength-trained athletes than sedentary people [37] . Endurance and strength are two characteristics of Basque ball.…”
Section: Discussionmentioning
confidence: 99%